1994
DOI: 10.1515/freq.1994.48.9-10.221
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of First-Order Digital Allpass Filter Sections

Abstract: In this paper all known first-order allpass sections with single multiplier and delay and limited to four adders are investigated. It is shown that most of the known sections are of a bridge (lattice) type and some new circuits of this type arc proposed. The sections are compared with respect to their multiplier coefficient sensitivities and roundoff noises, and general recommendations are formulated and families of curves are provided to be used for the selection of best circuit for given pole location and cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…1 that if a cascade realization of the FD allpass filters would be used, as the possible real pole positions are scattered all around the real axes, first-order allpass sections with low sensitivities for all these positions will be needed. About 20 such sections, including several newly developed, have been investigated and compared in (Stoyanov & Clausert, 1994) and it was shown that several low-sensitivity sections for every real poleposition could be found. We select to use four of them, shown in Fig.…”
Section: First Order Allpass Sectionsmentioning
confidence: 99%
“…1 that if a cascade realization of the FD allpass filters would be used, as the possible real pole positions are scattered all around the real axes, first-order allpass sections with low sensitivities for all these positions will be needed. About 20 such sections, including several newly developed, have been investigated and compared in (Stoyanov & Clausert, 1994) and it was shown that several low-sensitivity sections for every real poleposition could be found. We select to use four of them, shown in Fig.…”
Section: First Order Allpass Sectionsmentioning
confidence: 99%